2010
DOI: 10.1007/s00170-010-2902-1
|View full text |Cite
|
Sign up to set email alerts
|

State space modeling of non-proportional passive damping in machine tools

Abstract: In the context of virtual development processes of mechatronic systems like machine tools, the preventive assessment of the effects of light-weight structural components on the characteristics of controlled feed systems and therefore on the power- and energy requirement ofmachine tools is of great importance. The modelling of the damping is often limited in practical computation of real machine tools, because they are mostly limited to proportional damping characteristics. Yet the presence of discrete dampers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The viscous damping model is one of the most commonly used damping models. Several researchers have suggested that combined with the state-space method, a complex mode superposition method based on the viscous damping model can be realized, which can be applied to nonproportionally damped systems (De Domenico and Ricciardi, 2019; Foss, 1958; Igusa et al, 1984; Neugebauer et al, 2011; Papageorgiou and Gantes, 2010).…”
Section: Complex Mode Superposition Methods For a Nonproportionally Damped Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The viscous damping model is one of the most commonly used damping models. Several researchers have suggested that combined with the state-space method, a complex mode superposition method based on the viscous damping model can be realized, which can be applied to nonproportionally damped systems (De Domenico and Ricciardi, 2019; Foss, 1958; Igusa et al, 1984; Neugebauer et al, 2011; Papageorgiou and Gantes, 2010).…”
Section: Complex Mode Superposition Methods For a Nonproportionally Damped Systemmentioning
confidence: 99%
“…Thus, the viscous damping motion equations of these systems can be transformed to first-order differential equations by state-space modeling. The corresponding complex mode superposition method is obtained as a result of complex modal orthogonality (De Domenico and Ricciardi, 2019; Foss, 1958; Igusa et al, 1984; Neugebauer et al, 2011; Papageorgiou and Gantes, 2010). However, the construction of a reasonable damping matrix is very difficult (Clough and Penzien, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These variables are not only the material properties, but also the technical decisions, the design constraints, and the technological limits that might be accurately analysed using the real prototypes. [16,[25][26][27][28][29][30][31][32] Starting from the kinematic analysis of a milling machine that highlighted the main critical factors to damp vibrations, the static and dynamic properties have been analysed by using both finite element (FE) simulations and experimental tests. In particular, FE simulations allowed to improve the structure design, increasing structural indices and avoiding technical issues in prototype fabrication.…”
Section: Introductionmentioning
confidence: 99%